Cold EMR vs. Hot EMR for the removal of sessile serrated polyps larger than 10 mm: a systematic review and meta-analysis - Cong Ding; Jian-feng Yang; Xia Wang; Yi-feng Zhou; Hayat Khizar; Zheng Jin; Xiao-feng Zhang (BMC Surgery, 2024)
Abstract Background Endoscopic mucosal resection (EMR) appears to be a promising technique for the removal of sessile serrated polyps (SSPs) ≥ 10 mm. To assess the effectiveness and safety of EMR for removing SSPs ≥ 10 mm, we conducted this systematic review and meta-analysis. Methods We conducted a thorough search of Embase, PubMed, Cochrane, and Web of Science databases for relevant studies reporting on EMR of SSPs ≥ 10 mm, up until December 2023. Our primary endpoints of interest were rates of technical success, residual SSPs, and adverse events (AE). Results Our search identified 426 articles, of which 14 studies with 2262 SSPs were included for analysis. The rates of technical success, AEs, and residual SSPs were 100%, 2.0%, and 3.1%, respectively. Subgroup analysis showed that the technical success rates were the same for polyps 10–19 and 20 mm, and en-bloc and piecemeal resection. Residual SSPs rates were similar in en-bloc and piecemeal resection, but much lower in cold EMR (1.0% vs. 4.2%, P = 0.034). AEs rates were reduced in cold EMR compared to hot EMR (0% vs. 2.9%, P = 0.168), in polyps 10–19 mm compared to 20 mm (0% vs. 4.1%, P = 0.255), and in piecemeal resection compared to en-bloc (0% vs. 0.7%, P = 0.169). Conclusions EMR is an effective and safe technique for removing SSPs ≥ 10 mm. The therapeutic effect of cold EMR is superior to that of hot EMR, with a lower incidence of adverse effects. PROSPERO registration number CRD42023388959.